The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/08870446.2016.1174236
|View full text |Cite
|
Sign up to set email alerts
|

Social-cognitive antecedents of hand washing: Action control bridges the planning–behaviour gap

Abstract: Both motivational and volitional processes are important to consider in the improvement of hand hygiene practices. Moreover, the statistically significant effects for planning and action control illustrate the importance of these key self-regulatory factors in the prediction of hand hygiene. The current study highlights the importance of adopting models that account for motivational and volitional factors to better understand hand washing behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
55
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 38 publications
14
55
1
3
Order By: Relevance
“…Maintenance self-efficacy, on the other hand, is an optimistic belief during the post-actional (volitional) phase, where an individual perceives they have the competence and capability to persevere the formed action of behavior in the face of obstacles. A recent meta-analysis provided support for the HAPA constructs of planning and self-efficacy in predicting health behaviors [44], and previous research has also shown planning and self-efficacy to predict college students' hand washing [45,46] and sleep hygiene [47] more specifically.…”
Section: Introductionmentioning
confidence: 93%
“…Maintenance self-efficacy, on the other hand, is an optimistic belief during the post-actional (volitional) phase, where an individual perceives they have the competence and capability to persevere the formed action of behavior in the face of obstacles. A recent meta-analysis provided support for the HAPA constructs of planning and self-efficacy in predicting health behaviors [44], and previous research has also shown planning and self-efficacy to predict college students' hand washing [45,46] and sleep hygiene [47] more specifically.…”
Section: Introductionmentioning
confidence: 93%
“…This gap has been addressed through the recent integration of preparatory behaviors (Barz et al, 2016) and action control (Fernández et al, 2016). Preparatory behaviors are those formed a priori to the behavior, thus act as a sub-goal (Barz et al, 2016).…”
Section: Motivation and Volitionmentioning
confidence: 99%
“…Preparatory behaviors are those formed a priori to the behavior, thus act as a sub-goal (Barz et al, 2016). Action control refers to the monitoring and evaluation of action with respect to the behavior (Fernández et al, 2016). Preparatory behaviors, like planning strategies, are prospective routes to change; whereas action control involves concurrent strategies.…”
Section: Motivation and Volitionmentioning
confidence: 99%
“…Such plans to prevent possible lapses, coping planning, have been shown to be an important psychological determinant in the implementation of behavioural intentions, including in oral hygiene . However, planning alone is not always sufficient for behavioural initiation, with action control, a self‐monitoring of behaviour, being an essential element for putting those plans into practice . Planning is believed to function as a more distal volitional predictor, while action control is one that is more proximal to the behaviour .…”
Section: Introductionmentioning
confidence: 99%
“…In an intervention to stimulate action control, through the use of a diary to record floss usage, an increase in dental floss was observed . Some studies, not concerning oral hygiene, have gone farther, finding a relation between coping planning and action control sequentially mediating between intention and behaviour …”
Section: Introductionmentioning
confidence: 99%